Escuta musical via internet: contribuições para o ensino musical - Soares, Maria Cecília (2013)
This research had as its main objective to understand if the teachers who took part at ON LINE COURSE ,1B 1, an extension of the programme Find out About the Symphonic Orchestra of São Paulo, that took place in the first semester of 2012, could get some more musical improvement. This course EaD via Internet focussed on the appreciation of a better guided music repertoire whose main objective was to develop and improve a more attentive musical listening to teachers with no music knowledge. As a teacher/tutor of the course 1B1, it was important to analyse what advantages this on line course on music appreciation could bring to the learning of music, what would be the risks involved, and what contributions it would bring to the participants. With all these doubts, in the tutoring that lasted a term, three Forums took place focussing on activities on guided musical listening. We also used a guided activity related to the Parameters of sound, (loudness, intensity, duration, timbre) and another focussing on the listening of the high notes and a project on musical practice. We made use of qualitative and quantitative research in order to collect the data. The tool used for collecting the qualitative data was Wordle -Map of Clouds - and for the collecting of quantitative data, we used a tool found in Moodle called Task (the sending of a unique file was used for the collecting of the quantitative data). We also used a questionnaire to find out a bit about the participants profiles. To reach our objectives, we started our journey by analysing what music is, its origin and importance in Greek education, its transformation through digital means and the importance of MP3 file in this process. Adorno s, Moraes s and Santaella s writings helped us to discover the different types of emergent listeners and different ways to listen to music. Among other researchers, Almeida, Morin, Gohn, Sekeff , Fonterrada, Chizzoti and Freire have shown ways followed by Education as regards long distance education via internet, musical listening and the teaching of music. After having analysed the data, we could show that by developing an attentive listening via Internet, the teachers could understand and identify musical aspects. We also found out that although the teachers involved did not have any knowledge of the technical words of music, this lack did not interfere with the musical listening activity